Huakina Mai: A Kaupapa Māori Approach to Relationship and Behaviour Support. Issue 2 (10th November 2014) - Savage, Catherine; Macfarlane, Sonja; Macfarlane, Angus; Fickel, Letitia; Te Hēmi, Hēmi
<x content-type="archive" xml:space="preserve">Abstract</x> This article presents the developmental stages of a nationwide whole-school strengths-based behavioural intervention by Māori and centring on Māori interests; an initiative that has the potential to transform educational success and opportunities. The initial phase involved a cycle of data collection. This was conducted via a series of focus groups held with Māori specialists, practitioners, families and students, to support the development of a kaupapa Māori approach to school-wide positive behaviour. The evidence that was gathered indicated that a systems framework needed to emanate out of a Māori worldview, be inclusive of family and community, and support the notion that Māori children are able to learn as Māori — to enjoy positive cultural and identity development throughout their schooling. The findings in this article describe the core features that underscore how behaviour should be shaped and supported within schools, from a Māori perspective.